2012
DOI: 10.1007/s11357-011-9380-8
|View full text |Cite
|
Sign up to set email alerts
|

Diet mediates the relationship between longevity and reproduction in mammals

Abstract: The disposable soma hypothesis posits a negative correlation between longevity and reproduction, presumably because these aspects of fitness compete for a limited pool of nutrients. However, diet, which varies widely among animals, could affect the availability of key nutrients required for both reproduction and longevity, especially protein. We used a comparative database of mammal life history data to test the hypothesis that carnivores experience less of a negative relationship between reproduction and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Consuming a low proportion of protein in the diet relative to carbohydrate, not total calories, extended lifespan in ad libitum-fed flies (Bruce, et al 2013; Lee et al 2008), while diets with a higher proportion of protein shortened lifespan but improved reproduction (Lee et al 2008). This result has been replicated in several other insect species (Dussutour and Simpson 2009; Fanson, et al 2009; Grandison, et al 2009; Lee et al 2008; Piper et al 2011) and consistently indicates that the balance of macronutrients is the chief nutritional cue that directs metabolism towards longevity or reproduction (Wilder, et al 2012). A recent study in mice showed that ad libitum low protein, high carbohydrate diets fed short-term improved several markers of health including insulin, HOMA, glucose tolerance and triglycerides to a level comparable to CR, but without at 40% reduction in total calorie intake (Solon-Biet, et al 2015a).…”
Section: Macronutrient Balancementioning
confidence: 65%
“…Consuming a low proportion of protein in the diet relative to carbohydrate, not total calories, extended lifespan in ad libitum-fed flies (Bruce, et al 2013; Lee et al 2008), while diets with a higher proportion of protein shortened lifespan but improved reproduction (Lee et al 2008). This result has been replicated in several other insect species (Dussutour and Simpson 2009; Fanson, et al 2009; Grandison, et al 2009; Lee et al 2008; Piper et al 2011) and consistently indicates that the balance of macronutrients is the chief nutritional cue that directs metabolism towards longevity or reproduction (Wilder, et al 2012). A recent study in mice showed that ad libitum low protein, high carbohydrate diets fed short-term improved several markers of health including insulin, HOMA, glucose tolerance and triglycerides to a level comparable to CR, but without at 40% reduction in total calorie intake (Solon-Biet, et al 2015a).…”
Section: Macronutrient Balancementioning
confidence: 65%
“…It has long been recognized that dietary composition plays a deterministic role in overall health . Recent work has refocused attention on dietary protein, with special emphasis on how the concentration and composition of dietary protein affects ingestive behavior , energy balance , fecundity , and lifespan . The systems which sense and respond to changes in dietary protein remain poorly defined, but as EAAs cannot be synthesized endogenously, the ability to detect and respond to deficiencies in their supply represents an important survival mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Litter size is known to correlate with a number of other traits besides mammae number, including adult body mass (17), gestation length (18), dietary category (19), and environmental features (e.g., latitude (17), habitat type (20), geographic region (21), and climatic seasonality. (22)).…”
Section: Relative Predictive Strength Of Mammaementioning
confidence: 99%
“…Second, the studies that proposed the one-half and identity rules had limited taxonomic sampling to address mammalwide patterns (90 placental species (8), and 266 rodent species (7)), and they did not apply phylogenetic comparative methods, which are critical for evolutionary interpretations of character correlation (16). Finally, several other ecological and physiological traits are known to correlate with litter size in mammals (17)(18)(19)(20)(21)(22), raising questions about the explanatory power of the one-half and identity rules. Here we survey mammalian species diversity broadly and apply phylogenetic tests to ask (i) whether and how mammae number coevolves with litter size across Mammalia and (ii) how mammae number compares to other known predictors of litter size.…”
Section: Introductionmentioning
confidence: 99%